METHODOLOGICAL APPROACH TO THE INSTITUTIONALIZATION OF LAND RELATIONS ON THE PRINCIPLES OF ECOLOGICAL-ECONOMIC IMPERATIVES - Dorosh, J. M. (Land Management, Cadastre and Land Monitoring, 2012)
Carrying out institutional changes in the land relation in the direction of harmonization of economic, ecological and social target reference points is proved, and also offers on algorithmization of this process on the basis of ecology-economic imperativws are created.